Comparison of methods of non-mechanical pressure measurement in the cuff of an endotracheal tube - Sadovyi , Valentyn; Kuchyn , Iurii (The Ukrainian Scientific Medical Youth Journal, 2024)
Bronchoscopy is a diagnostic and follow-up procedure. Despite the fact that this manipulation itself is minimally invasive, it can be a difficult test for both the patient and the doctor. Therefore, this manipulation definitely requires anesthesia and sedation. This study compared dexmedetomidine and propofol sedation methods during diagnostic bronchoscopy to assess their safety, effectiveness, and satisfaction. The results show a high level of safety of both methods, although some significant differences affecting the choice of sedation method were found. 32 patients participated in the study, divided into two groups depending on the used method of sedation: propofol or dexmedetomidine. Pulse oximetry, heart rate, capnography parameters were measured, the number and severity of iatrogenic lesions of the trachea, as well as the satisfaction of care and doctors were assessed. In some groups, there was a high level of safety of sedation. Dexmedetomidine sedation was associated with fewer cough episodes and greater satisfaction, but had a longer induction time with propofol. A low incidence of serious complications was observed in both groups. Dexmedetomidine can be considered a safe and effective sedation option for diagnostic bronchoscopy, offering additional benefits such as reduced cough episodes and increased patient satisfaction. The choice of the sedation method is based on the individual characteristics of the patient and the available resources of the hospital.